2017
DOI: 10.1016/j.jaci.2016.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-evoked cough responses in asthmatic patients: Evidence for airway neuronal dysfunction

Abstract: Patients with stable asthma exhibited exaggerated capsaicin-evoked cough responses consistent with neuronal dysfunction. Nonatopic asthmatic patients had the highest cough responses, suggesting this mechanism might be most important in type 2-low asthma phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 30 publications
3
88
2
2
Order By: Relevance
“…The number of coughs in the 15 seconds following each inhalation was counted The challenge continued until the maximum tolerated dose or the final concentration was inhaled (6,22). The maximum number of coughs evoked at any concentration (E max ) was the main endpoint, but the concentration evoking 50% of the maximal response (ED 50 ) was also reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of coughs in the 15 seconds following each inhalation was counted The challenge continued until the maximum tolerated dose or the final concentration was inhaled (6,22). The maximum number of coughs evoked at any concentration (E max ) was the main endpoint, but the concentration evoking 50% of the maximal response (ED 50 ) was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the threshold for provoking cough by capsaicin (C2 or the C5 concentration of capsaicin required to elicit at least 2 or 5 coughs, respectively) has been found to be lowered in various populations of patients with Chronic Obstructive Pulmonary(4,26), asthma (22,26), Idiopathic Pulmonary Fibrosis (27) and also refractory chronic cough patients(4,5,28) compared to healthy controls. These data imply that TRPV1 function is frequently increased in a disease setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the divergent profile of tussive responses described in clinical challenge studies among patients with different chronic lung diseases and even in patients within one disease group (e.g. asthma) supports the hypothesis of disease-specific neurophenotypes [35,38]. As such it will become necessary to identify which patient subgroups may be more susceptible to therapeutics targeting neuronal hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the threshold for provoking cough by capsaicin (often referred to as the C2 or the C5: concentration of capsaicin required to elicit two or five coughs, respectively) has been found to be lowered in various populations of COPD [33][34][35], asthmatic [33, [35][36][37][38][39], IPF [40] and chronic idiopathic cough [35,41] patients who have chronic cough compared to healthy controls. These data imply that TRPV1 function is increased in a disease setting.…”
Section: Trpv1mentioning
confidence: 99%
“…For example, the interactions between bronchospasm and cough are poorly understood. Our previous work in stable asthma has demonstrated that cough responses to citric acid and capsaicin are not correlated with methacholine BHR or FEV 1 1 2. The effects of acute bronchoconstriction on cough responses evoked by capsaicin inhalation have only been studied in healthy volunteers where minimal bronchoconstriction (mean FEV 1 fall 8.8%) had no effect on the capsaicin concentration provoking two coughs (C2) 3.…”
Section: Introductionmentioning
confidence: 99%